Cognitive Dissonance and the Image Pesantren in Pekalongan: A Study Using Mixed Methods Approach - Dyatmika, Teddy; Mardiani, Wahyuni (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2024)
News coverage of violence in pesantren has increased. The news coverage should have made the image of pesantren hostile, and the number of students decreased. However, pesantren and Santri in Pekalongan Regency have experienced a significant increase. This study aimed to analyze the community in overcoming cognitive dissonance when sending their children to pesantren and to analyze the exposure to negative news on parents' interest in sending their children to pesantren through the intervening variable of the image of pesantren. The theory used is cognitive dissonance. The research methodology uses a post-positivistic paradigm with a mixed methods approach. The population was 976,504 people, and a sample of 475 respondents with a simple random technique. The data collection method used surveys and in-depth interviews. The study's results showed that the community could reduce cognitive dissonance; they considered pesantren the safest places to deepen religious knowledge, train independence, and make many friends. Parents assume that not all pesantren experience physical violence and sexual violence. The second research result is that the influence of mass media exposure on parents' request to send their children to pesantren is minimal, only 7.29%. In comparison, the image of pesantren influences parents' interest in sending their children to pesantren by 26.21%. Together, mass media exposure and the image of pesantren influence parents' interest in sending their children to pesantren by 34.8%. Meanwhile, mass media exposure does not affect parents' interest in sending their children to pesantren through the intervening variable of pesantren image. Pemberitaan kekerasan di pesantren meningkat. Pemberitaan membuat citra pesantren harusnya menjadi negatif dan jumlah Santri berkurang. Akan tetapi, pesantren dan Santri di Kabupaten Pekalongan mengalami peningkatan signifikan. Tujuan penelitian ini menganalisis masyarakat dalam mengatasi disonansi kognitif saat memondokkan anaknya di pesantren dan menganalisis terpaan pemberitaan negatif terhadap minat orang tua memondokkan anaknya di pesantren melalui variabel intervening citra pesantren. Teori yang digunakan adalah disonansi kognitif. Metodologi penelitian menggunakan paradigma post-positivistik dengan pendekatan mixed methods. Populasi sejumlah 976.504 masyarakat dan sampel 475 responden dengan teknik random sederhana. Metode pengambilan data menggunakan survei dan wawancara mendalam. Hasil penelitian menunjukkan masyarakat dapat mengurangi disonansi kognitif, mereka menganggap bahwa pondok pesantren adalah tempat yang paling aman untuk memperdalam ilmu agama, melatih kemandirian dan memperoleh banyak teman. Orang tua beranggapan tidak semua pesantren terjadi kekerasan fisik dan kekerasan seksual. Hasil penelitian yang kedua yaitu pengaruh terpaan media massa terhadap minat orang tua memondokkan anak di pesantren sangat kecil hanya 7,29% sedangkan citra pesantren memberikan pengaruh terhadap minat orang tua memondokkan anak di pesantren sebesar 26,21%. Secara bersama-sama terpaan media massa dan citra pondok memberikan pengaruh sebesar 34,8% terhadap minat orang tua memondokkan anak di pesantren. Sedangkan terpaan media massa tidak memberikan pengaruh terhadap minat orang tua memondokkan anak di pesantren melalui variabel intervening citra pesantren.